Parking System Using Nodemcu Microcontroller Based Infrared Sensor - Arifin, Muhammad; Muchlas, Muchlas (Association for Scientific Computing Electrical and Engineering (ASCEE), 2021)
Vehicles are one of the important things in supporting the mobility of people and goods quickly, safely and comfortably. Cars are one of the most widely used types of vehicles because they can accommodate many people or goods. This study aims to make a prototype of an organized parking lot so that it is easier for car users to find parking. The system in this study uses a NodeMCU microcontroller as the controller. Infrared sensors are used as sensors to detect the state of the parking area. The system has two outputs in the form of an LED and a website. Infrared sensors can detect all parking area conditions, LEDs run according to parking area conditions, and the website can be used as remote monitoring of the parking area of this system. Parking area users can easily find an empty parking area.